Transforming Arabic Language Learning in the Era of Industry 5.0: Integrating Digital Technology and Humanistic Approaches - Dina Indriana; Hannanah Mukhtar (Fakultas Tarbiyah dan Keguruan, 2025)
Purpose – This study aims to formulate adaptive and innovative Arabic language learning strategies in the Industrial Revolution 5.0 era by synergizing advanced digital technology with humanistic values. It specifically explores the utilization of various digital platforms and identifies the pedagogical challenges faced by educators in bridging the gap between technological potential and field reality. Design/methods/approach – The research employs a descriptive qualitative method. Data were collected through in-depth interviews, classroom observations, and documentation involving seven Arabic language teachers from State Islamic Senior High Schools (MAN) across Serang City, selected via simple random sampling. The data were analyzed using the Miles and Huberman interactive model, including data reduction, display, and conclusion drawing. Findings – The results indicate that the integration of digital ecosystems—such as AI-based platforms, chatbots, and interactive web tools—has successfully created a flexible and dynamic learning environment for Generation Z. However, implementation is significantly hindered by disparities in teachers' digital literacy, administrative burdens, and structural infrastructure limitations. The study finds that while technology enhances engagement, the teacher's role remains irreplaceable as a humanistic facilitator who provides cultural context and motivation. Research implications – The success of Arabic learning in this era depends on a